KEMAMPUAN MENGGUNAKAN IDIOM DALAM KALIMAT PESERTA DIDIK SMP NEGERI 1 TUTALLU KABUPATEN POLEWALI MANDAR - Muthmainnah Muthmainnah (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2012)
This study aimed to describe the ability to use idioms in sentences VIII.D grade students of SMP Negeri 1Tutallu. The study design used is dsekriktif. The population in this study is VIII.D grade students of SMP Negeri 1 Tutallu who was 23 people. The sample was the entire population or using the total sample. The collection of data through tests, interviews and observations. The results showed that the ability to use idioms in sentences VIII.D grade students of SMP Negeri 1 Tutallu Polewali Mandar categorized able to score an average of 83.40. This is evident from the results of data analysis showed that among 23 samples including 11 categories capable learners or approximately 47.82% of learners achieved by 2 or by 8.69%. For category 7 is able to successfully achieved by learners or by 30.43%. and category 3 sufficiently achieved by the students or by 3:04%. VIII.D class participants categorized as capable with an average value of 83.47%.